Evaluation of abdominal compression band for pediatric postural tachycardia syndrome: a crossover study - Yamawake, Ginroku; Yoshida, Seiji; Tanaka, Hidetaka; Kurooka, Yusuke; Kubo, Atsuko; Ota, Yoshitaka; Mizutani, Midori; Ashida, Akira (Frontiers in Pediatrics, 2025)
BackgroundAbdominal compression is an effective nonpharmacological treatment for orthostatic intolerance. Although the efficacy of abdominal compression bands has been studied in adults, studies involving children are limited. This study investigates the efficacy of abdominal compression bands in children diagnosed with postural tachycardia syndrome (POTS), using a larger cohort and incorporating autonomic nervous function assessment via frequency analysis.MethodsA crossover study was conducted with 23 patients with POTS (mean age 13.4 ± 0.8 years), with and without abdominal compression bands (20 mmHg). Standing symptoms, hemodynamics (blood pressure, heart rate [HR], cardiac index [CI], stroke volume [SV], and total peripheral resistance [TPR]), and cardiovascular autonomic function were assessed by spectrum analysis during standing tests. These variables were compared with and without bands.ResultsWhen standing with the abdominal compression band, subjective symptoms improved, increases in heart rate (HR) and decreases in stroke volume (SV) were suppressed, blood pressure was maintained, and cardiac parasympathetic function was improved. By contrast, in the supine position, patients showed an increased HR, decreased CI, increased TPR, lower cardiac parasympathetic function, and higher cardiac sympathetic function.ConclusionAbdominal compression bands may relieve symptoms while standing and improve hemodynamic and autonomic nervous functions in children with POTS.